长期日晒与组蛋白乙酰化变化有关. (19th July 2018) - Ding, S.; Chen, J.; Zeng, Q.; Lu, J.; Tan, L.; Guo, A.; Kang, J.; Yang, S.; Xiang, Y.; Zuo, C.; Huang, J.
Abstract : Linked Article:  Ding et al. Br J Dermatol 2018;179 :110–117